Hypofibrinogenaemia with Compound Heterozygosity for Two γ Chain Mutations – γ 82 Ala→Gly and an Intron Two GT→AT Splice Site Mutation - Wyatt, Jane; Brennan, Stephen O.; May, Stephen; George, Peter M. (Thrombosis and Haemostasis, 2000)
We investigated the molecular basis of hypofibrinogenaemia in a woman with a history of recurrent, pregnancy-associated bleeding, and miscarriage. She had a Clauss fibrinogen of 0.9 mg/ml and SDS PAGE of purified fibrinogen showed a normal pattern of chains. However careful inspection of reverse phase chain separation profiles showed apparent homozygosity for a more hydrophilic form of the γ chain. DNA Sequencing showed only heterozygosity for a CGT→GGT (Ala→Gly) mutation at codon γ82, but further sequencing showed an additional GT splice sequence mutation at the 5’ end of intron 2 of the γ gene. Translation of mRNA containing this intron would result in premature truncation explaining the phenotypic homozygosity of the γ82 Ala→Gly substitution. The patient’s sister had a mild bleeding disorder with hypofibrinogenaemia and she too was a compound heterozygote for the γ mutations. Her nephew had only the novel splice site mutation, while her mother and daughter inherited only the γ82 Ala→Gly substitution.
Keywords: Fibrinogen; hypofibrinogenaemia; mutation; compound heterozygote